Condições de saúde bucal de crianças e adolescentes portadores de síndrome de Down - Messias, Leciana Paula de Angelis [UNESP]; Landucci, LuÍs Fernando; Vasques, Ana Maria Veiga [UNESP]; Bosque, Aline Valsechi; Schweitzer, Christiane Marie; Okamoto, Ana Cláudia [UNESP]; Jardim Júnior, Elerson Gaetti [UNESP] (My University, 2011)
Patients with Down syndrome have shown different conditions of oral health, and there is a low occurrence of dental caries and a higher susceptibility to periodontal diseases. Thus, this study aimed to evaluate the prevalence of dental caries and periodontal diseases in subjects with Down syndrome. The population was composed of 40 patients with the syndrome, aged 6 to 18 years, of both genders, and an equal number of non-syndromic patients. The periodontal conditions were evaluated by mean of the criteria of PSR and dental conditions were registered following indexes dmft and DMFT. It was found that in children with Down syndrome, the dmft index was 1.17 and DMFT 3.53 while the control group was verified dmft 1.97 and DMFT 2.77. The results of PSR evidenced that 32.5% of children with Down syndrome were periodontally healthy, 65% were gingivitis patients and 2.5% were periodontitis patients, while in the control group, 50% healthy and 50% were gingivitis patients. The results evidenced similar populations of cariogenic cocci between patients with Down syndrome and non-syndromic subjects. It was concluded that the incidence of caries in children with Down syndrome was higher in permanent teeth compared with the control group, while in the occurrence of deciduous teeth caries was slightly higher in the control group, so when children with Down syndrome are subjected to periodic examinations, they present themselves periodontally healthy.

Os pacientes com síndrome de Down têm mostrado diferentes condições de saúde bucal, destacando-se uma baixa ocorrência de cárie e maior suscetibilidade às doenças periodontais. Assim, o presente estudo objetivou avaliar a prevalência de cárie e de patologias periodontais em portadores de Síndrome de Down. A população foi constituída de 40 pacientes portadores da síndrome, com idade de 6 a 18 anos, de ambos os gêneros, e igual número de pacientes não sindrômicos, os quais foram submetidos ao exame clínico periodontal segundo os critérios do PSR para determinação do índice de cárie empregando-se os índices ceo-d e CPOD. Verificou-se que nas crianças com síndrome de Down o índice médio ceo-d foi 1,17 e o CPO-D 3,53 enquanto que no grupo controle foi observado ceo-d 1,97 e o CPOD 2,77. Verificou-se que 32,5% das crianças com síndrome de Down eram saudáveis, 65% com gengivite e 2,5% com periodontite e, no grupo controle, 50% foram saudáveis e 50% mostraram gengivite. Os resultados evidenciaram que a população de cocos cariogênicos foi similar entre pacientes portadores ou não de síndrome de Down. Concluiu-se que a ocorrência de cárie em crianças com síndrome de Down foi maior nos dentes permanentes comparadas com o grupo controle, enquanto que na dentição decídua a ocorrência de cárie foi maior no grupo controle, assim quando crianças com síndrome de Down são submetidas a exames periódicos, elas apresentam-se periodontalmente saudáveis.
Oral health conditions of children and adolescents with Down syndrome
Keywords: Dental caries; Down syndrome; DMFT index; CRP; Cárie dental; Síndrome de Down; Índice CPOD; PCR